Structural and thermodynamic evolution of an amorphous SiOC ceramic after swift heavy ion irradiation. (1st January 2023) - Niu, Min; Jayanthi, K.; Gao, Hongfei; Solomon, Alexandre P.; O'Quinn, Eric C.; Su, Lei; Qin, Yuanbin; Toimil-Molares, Maria Eugenia; Wang, Hongjie; Lang, Maik; Navrotsky, Alexandra
Abstract: Radiation induced structural and energetic changes have been widely studied in crystalline materials, but studied to a much lesser extent in amorphous solids. Using a combination of neutron pair distribution function (PDF) analysis and high temperature oxide melt solution calorimetry, we obtained critical insights into the structural and energetic evolution in a swift heavy ion irradiated amorphous SiOC polymer-derived ceramic. The radiation modified SiOC structure becomes energetically less stable by 24.0±1.6 kJ/mol compared to the unirradiated structure. This destabilization is related to decreased connectivity of the Si-O-C network and destruction of free carbon. In comparison with unirradiated SiOC, the irradiated structure is more likely to become phase separated during subsequent thermal annealing. Our study has important implications for evaluating amorphous SiOC ceramic as a possible radiation resistant structure for nuclear applications. Graphical Abstract: Image, graphical abstract